Route of Delivery Modulates the Efficacy of Mesenchymal Stem Cell Therapy for Myocardial Infarction: A Meta-Analysis of Preclinical Studies and Clinical Trials - Kanelidis, Anthony J; Premer, Courtney; Lopez, Juan; Balkan, Wayne; Hare, Joshua M (Circulation research, 2017)
Accumulating data support a therapeutic role for mesenchymal stem cell (MSC) therapy; however, there is no consensus on the optimal route of delivery. We tested the hypothesis that the route of MSC delivery influences the reduction in infarct size and improvement in left ventricular ejection fraction (LVEF). We performed a meta-analysis investigating the effect of MSC therapy in acute myocardial infarction (AMI) and chronic ischemic cardiomyopathy preclinical studies (58 studies; n=1165 mouse, rat, swine) which revealed a reduction in infarct size and improvement of LVEF in all animal models. Route of delivery was analyzed in AMI swine studies and clinical trials (6 clinical trials; n=334 patients). In AMI swine studies, transendocardial stem cell injection reduced infarct size (n=49, 9.4% reduction; 95% confidence interval, -15.9 to -3.0), whereas direct intramyocardial injection, intravenous infusion, and intracoronary infusion indicated no improvement. Similarly, transendocardial stem cell injection improved LVEF (n=65, 9.1% increase; 95% confidence interval, 3.7 to 14.5), as did direct intramyocardial injection and intravenous infusion, whereas intracoronary infusion demonstrated no improvement. In humans, changes of LVEF paralleled these results, with transendocardial stem cell injection improving LVEF (n=46, 7.0% increase; 95% confidence interval, 2.7 to 11.3), as did intravenous infusion, but again intracoronary infusion demonstrating no improvement. MSC therapy improves cardiac function in animal models of both AMI and chronic ischemic cardiomyopathy. The route of delivery seems to play a role in modulating the efficacy of MSC therapy in AMI swine studies and clinical trials, suggesting the superiority of transendocardial stem cell injection because of its reduction in infarct size and improvement of LVEF, which has important implications for the design of future studies.